Marriage in Morocco: A Practices of The Mudawwanatul Usrah Law in The Land of Guardians - Nasiri Nasiri (International Journal of Islamic Thought and Humanities, 2022)
Morocco is a country that has combined the opinions of several schools in achieving the information contained in Islamic law that exists in the country of Morocco from some of the issues that were reformed in the Family Law (2004) in Morocco, as has already existed in other Islamic countries. Regulations related to marriage are almost the same as Indonesia, it could be due to the Compilation of Islamic Law (KHI) in Indonesia reflecting on Mudawwanat al-Usrah in Morocco or it can also be influenced by the Moroccan community with Indonesian society equally winged Ahl al-Sunnah wa al-Jama'ah (ASWAJA), in Morocco the Maliki Perspective which can guide and in Indonesia the Syafi'i Perspective which is a role model Moroccan society upholds the values ​​of tradition and local wisdom. They also like the beauty and love of traditional entertainment as long as it does not conflict with the basic principles in the teachings of Islam that they profess.